PERLINDUNGAN HKI SEBAGAI UPAYA PEMENUHAN HAK ATAS IPTEK, BUDAYA DAN SENI - Sri Imaniyati, Neni (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2010)
The problem of Intellectual Property Right (IPR) is getting more complicated. IPR becomes one of the international issues besides problems on human right, environment, democratization, and standardization. Based on basic concept of IPR, IPR is the effort of recognition, respect, and right fulfillment on science, technology, culture, and art, which are parts of human rights. The IPR regulation in Indonesia is hierarchically written on the constitution and other regulations. As the consequence, when Indonesia ratified GATT, the IPR regulation in Indonesia must be continuously in line with TRIPs. Today, Indonesia is considered unready to implement TRIPs. It then turns out as negative perception upon IPR that is the possibility of losing the chance of IPR implementation in Indonesia that closely related to the emergence of high cost, insignificant influence on the foreign investment in Indonesia, and the occurrence of âbiological hijackâ toward Indonesian natural resources.Keywords: Protection, IPR, Science, Technology, Art and Culture